Perspectives on care at home for older people - Ceci, Christine.; Kristín Björnsdóttir.; Purkis, Mary Ellen. (Routledge studies in health and social welfare ;, 2012)
"This volume focuses on how high quality care is provided and the practices and policies that support this. It will offer case studies (both policy- and practice-oriented empirical studies) from countries that share a basic orientation to social welfare: Canada, Denmark, Finland, Iceland, Sweden and the United Kingdom. This book will be essential reading for students, practitioners and researchers who wish to understand diverse problems in service provision for the elderly and the complexities of policy responses in different health and social care contexts"--